2018
DOI: 10.7752/jpes.2018.s146
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The article is devoted to the search of the new, modern and effective methods for conducting the physical education classes for the students. The effectiveness of these methods is determined by an increase in the level of the development of the basic physical qualities and an increase in the volume of the motor activity of those who are engaged in it. The possibility of using the Kangoo Jumps exercise complexes on the physical education classes with the female students with an experience in aerobic exercise is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…The results of the step-test for females of group 3 (Kangoo Jumps fitness) were significantly higher than the results of other female students. The recovery intervals of females practicing fitness aerobics and Kangoo Jumps fitness were compared in similar studies [32]. The results are different from our data.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The results of the step-test for females of group 3 (Kangoo Jumps fitness) were significantly higher than the results of other female students. The recovery intervals of females practicing fitness aerobics and Kangoo Jumps fitness were compared in similar studies [32]. The results are different from our data.…”
Section: Discussioncontrasting
confidence: 59%
“…Fitness aerobics classes involve performing rhythmic dance movements to music with a certain level of intensity [28]. However, in the process of teaching female students to various dance movements, the intensity of the load is not high [32]. There is data concerning the targeted increase in the intensity of aerobic exercise in young people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that these kinds of equipments affect and regenerate postural control variables and improve some physical-physiological parameters (strength, flexibility, endurance, muscle strength) and as a result of this, there is an increase about the levels of well-being and life satisfaction of the participants (Baltaretu, 2015). Regarding trainings with KJ shoes, there are studies with significant difference in the literature (Akın and Durmuş, 2014;deOliveira et al, 2014;Germina et al, 2015;Mokrova et al, 2018). In studies conducted to learn how they react to the trainings done on soft and hard ground to improve the balance skills of the hearing-impaired individuals, it was reported that posture exercises on the surface of the bosu ball are effective for developing balance skills along with visual stimuli (Yaggie and Campbell, 2006;Lubetzky-Vilnai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Podlesny ( In his research, A.I. Podlesny stated that the motivation for professional and applied physical training of students learning the boatmaster trade was influenced by the propensity to choose the trade, the need to achieve, the motivation to focus on success (Tatyana Mokrova, 2018).…”
Section: Discussionmentioning
confidence: 99%